Barreiras da logística reversa de óleos lubrificantes : uma avaliação utilizando a análise hierárquica de processos - Comper, Indiana Caliman (2017)
In Brazil, legally, the only proper disposal of Used or Contaminated Lubricating Oil (OLUC, in Portuguese) is the recovery of the initial properties and reuse by means of “rerefing”. For this to happen efficiently and satisfactorily, a whole reverse logistics system needs to work. However, there are a number of barriers that compromise the full realization of OLUC's reverse logistics and, consequently, its adequate destination. By detailed bibliographical review and documentary analysis, political barriers (failures in legislation, evolution of collection targets, scope of inspection and illegal destination of OLUC), infrastructure barriers (geographic dimensions of Brazil, inefficient transportation infrastructure, collection network and the quantity and geographic distribution of “re-refineries”), market barrier (uncertainties in the quality of the returned OLUC) and socioenvironmental barrier (lack of awareness about OLUC's reverse logistics / behavioral and social issues) were identified. Based on the identified barriers, a Current Reality Tree (CRT) was then constructed to represent the cause and effect relationship between the barriers, pointing out that the possible root causes for the difficulty in the operationalization of OLUC's reverse logistics are: lack of awareness about the OLUC’s reverse logistics, the geographical dimensions of Brazil and the failures in legislation. Finally, an Analytic Hierarchy Process (AHP) was performed, which identified that the coverage of the collecting network is the barrier that most compromises OLUC's reverse logistics, in the analysis of experts and researchers, indicating that the main action to be taken for improvement the OLUC's reverse logistics in Brazil is that the collecting network expands to all brazilian cities and contemplate all OLUC generating points. Thus, this work presents an important contribution to the research in this area, because it made possible to structure the problem and, thus, to identify the barriers that compromise the OLUC's reverse logistics, to interrelate these barriers and finally to hierarchize them, identifying those that compromise with more or less force, the realization of the reverse logistics of lubricating oils.